Identity in Question. - Elliott, Anthony, 1964- (Sage Publications, 2009)
A spectacular collection of essays by the most noted theorists of identity. The book well frames the issues around identity that presently are defining living in the early 21st century A must read' - Patricia Ticineto Clough, City University, New York. 'A wonderfully disparate and impressively distinguished set of authors to address the question of identity. The result is exciting and fruitful. No other book connects so elegantly sociological notions of individualization with the psychoanalysis of melancholy' - Scott Lash, Goldsmiths College, University of London. 'A series of cutting-edge pap.